The importance of speckle tracking echocardiography in the evaluation of cardiac functions in patients with rheumatoid arthritis - Müşerref Ebik,; Nurettin Taştekin,; Muhammet Gürdoğan,; Mustafa Ebik,; Murat Birtane,; Hakan Emmungil,; Barış Yılmazer,; Necdet Süt, (Archives of Rheumatology, 2024)
Objectives: In this study, we aimed to analyze the layer-specific strain values obtained by speckle tracking echocardiography (STE) method in the determination of subclinical cardiac dysfunction in rheumatoid arthritis (RA) patients. Patients and methods: Between February 2019 and October 2019, a total of 63 female RA patients (mean age: 51.82±6.07 years; range, 40 and 65 years) who had a confirmed diagnosis were included. Thirty-one age-matched female healthy individuals (mean age: 50.71±5.37 years; range, 40 and 65 years) were selected as the control group. The patients were divided into three groups according to the duration of disease as <5 years, 5-10 years and >10 years. The Disease Activity Score in 28 joint - C-reactive protein (CRP) was used to determine disease activation. The standard assessment included complete serum CRP, anti-cyclic citrullinated peptide, rheumatoid factor, N-terminal pro B-type natriuretic peptide (NT-proBNP), and homocysteine. Global longitudinal strain (GLS) analysis was performed with STE. Results: The NT-proBNP values were found to be higher in RA patients compared to the control group (p=0.044). In terms of conventional echocardiographic parameters, a significant difference between E/A and E/E’ ratios was observed (p<0.001 and p=0.015). Endocardium, transmural, and epicardium GLS values obtained by STE were found to be lower in RA patients (p<0.05). The left ventricular (LV) GLS values worsened, as the duration of disease increased (p<0.05). There was a significant correlation between RA disease activity and LV GLS values, showing that increasing levels of disease activity was associated with worse LV GLS (r=0.583, p<0.01 and r=0.681, p<0.01 and r=0.689, p<0.01 for endocardium, transmural and epicardium, respectively). Conclusion: Our study results suggest that the layer-specific GLS values obtained by STE decrease in RA patients.